Jim Butcher's The Dresden files. Down town. Volume 1 - Butcher, Jim, 1971-; Powers, Mark (Comics author) (Butcher, Jim, 1971- Dresden files., 2015)
Wizard-for-hire Harry Dresden and his new apprentice intend to stop the havoc created in the Windy City by a mad sorcerer.